Embracing Change and Refraction: A Prism Through Pandemic Times - Nellis, Robert Christopher; Ricketts, Kathryn Ann (Journal of the Canadian Association for Curriculum Studies, 2024)
This special issue initially arose from the 2019 Provoking Curriculum Studies Conference at the University of Regina. Shortly after the conference, the world was thrown into the COVID-19 pandemic. The papers in this special issue view the pandemic through a prism to consider existing practices within the academy and reflect upon and imagine new possibilities for academic work and lives. Author explorations include arts-based inquiry, grief, peer-to-peer support, Indigenous Métissage, poetic inquiry and diasporic bodies.